Loading...

6 squared plus 3 is equal to 39.

3

6 squared is 36. 36 plus 3 is 39

40

That factors to (2c + 3)(3c + 2)

(5x + 2)(x + 3)

(x + 3)(x + 2)

It is 36/6 +4 = 10

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.

2(x + 3)(x + 1)

1/2 = 25/50

15.

(x + 3)(x + 2)

5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5

2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)

6x^2 -13x+6 = (3x-2)(2x-3) when factorized

6 squared plus 9 squared is equal to 117.

8 + X SQUARED

8

(2x - 3)(x + 2)

(x + 3)(x - 2)

(x-3)(x-2)

(x + 3)(5x - 2)

(2x - 3)(x + 2)

62 + 2 = 38